Provision of services in primary care for type 2 diabetes: a qualitative study with patients, GPs, and nurses in the East of England - Dambha-Miller, Hajira (Br J Gen Pract, 2020)
BACKGROUND: There is little evidence on the impact of national pressures on primary care provision for type 2 diabetes from the perspectives of patients, their GPs, and nurses. AIM: To explore experiences of primary care provision for people with type 2 diabetes and their respective GPs and nurses. DESIGN AND SETTING: A qualitative primary care interview study in the East of England. METHOD: Semi-structured interviews were conducted, between August 2017 and August 2018, with people who have type 2 diabetes along with their respective GPs and nurses. Purposive sampling was used to select for heterogeneity in glycaemic control and previous healthcare experiences. Interviews were audio-recorded and analysed thematically. The consolidated criteria for reporting qualitative research were followed. RESULTS: The authors interviewed 24 patients and 15 GPs and nurses, identifying a changing landscape of diabetes provision owing to burgeoning pressures that were presented repeatedly. Patient responders wanted GP-delivered care with continuity. They saw GPs as experts best placed to support them in managing diabetes, but were increasingly receiving nurse-led care. Nurses reported providing most of the in-person care, while GPs remained accountable but increasingly distanced from face-to-face diabetes care provision. A reluctant acknowledgement surfaced among GPs, nurses, and their patients that only minimum care standards could be maintained, with aspirations for high-quality provision unlikely to be met. CONCLUSION: Type 2 diabetes is a tracer condition that reflects many aspects of primary care. Efforts to manage pressures have not been perceived favourably by patients and providers, despite some benefits. Reframing expectations of care, by communicating solutions to both patients and providers so that they are understood, managed, and realistic, may be one way forward.